2017
DOI: 10.1039/c7tb00150a
|View full text |Cite
|
Sign up to set email alerts
|

Janus nanoparticles for T cell activation: clustering ligands to enhance stimulation

Abstract: The in vitro activation of T cells by synthetic particles is a promising technique for adoptive cancer immunotherapy. While it is known that cell-surface receptors form clusters during T cell activation, the use of clustered ligands on synthetic particles to modulate T cell response is a largely unexplored concept. Building upon our previous finding that T cells respond differently to various micro-sized patterns of ligands, we here investigate the effect of nano-sized ligand clusters on T cell activation. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Regarding the use of antibody-decorated nanoparticles to activate T cells, different parameters such as surface density and spatial arrangement of these antibodies on the nanoparticle, as well as their amount, should be considered. A recent work has concluded that Janus-type nanoparticles with clustered ligands produced a better T cell activation than nanoparticles homogeneously decorated with the same amounts of ligands [85]. This result could be explained by the co-existence of multiple ligand-receptor interactions in the cluster conformation, which enhances the signal transduction in the lymphocyte.…”
Section: Nanoparticles To Enhance the Antitumoral Action Of Adaptive mentioning
confidence: 99%
“…Regarding the use of antibody-decorated nanoparticles to activate T cells, different parameters such as surface density and spatial arrangement of these antibodies on the nanoparticle, as well as their amount, should be considered. A recent work has concluded that Janus-type nanoparticles with clustered ligands produced a better T cell activation than nanoparticles homogeneously decorated with the same amounts of ligands [85]. This result could be explained by the co-existence of multiple ligand-receptor interactions in the cluster conformation, which enhances the signal transduction in the lymphocyte.…”
Section: Nanoparticles To Enhance the Antitumoral Action Of Adaptive mentioning
confidence: 99%
“…At the lower end of the size spectrum, Lee and Yu prepared 500 nm silica Janus particles using a microcontact printing procedure with azide functionalized SiNPs followed by side‐specific antibody attachment via amine‐carboxylate carbodiimide chemistry. The covalently attached antibodies were thereafter shown to selectively target CD3 and CD25 receptors on T‐cells . Tang et al prepared bifunctional 2.0–4.5 µm silica and polystyrene Janus particles using a metal deposition technique followed by the orthogonal approaches of carbodiimide chemistry and biotin–streptavidin binding for protein functionalization at the respective faces.…”
Section: Introductionmentioning
confidence: 99%
“…The covalently attached antibodies were thereafter shown to selectively target CD3 and CD25 receptors on T-cells. [4] Tang et al prepared bifunctional 2.0-4.5 µm silica and polystyrene Janus particles using a metal deposition technique followed by the orthogonal approaches of carbodiimide chemistry and biotin-streptavidin binding for protein functionalization at the respective faces. [7b] Similarly, Bradley et al presented 850 nm Janus particles with multiple clickable polystyrene and poly(propargyl acrylate) sides using thiol-yne click chemistry for conjugation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations